Central Exams and Adult Skills: Evidence from PIAAC - Lisa Leschnig; Guido Schwerdt; Katarina Zigova (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Central exams are often hypothesized to favorably affect incentive structures in schools. Indeed, previous research provides vast evidence on the positive effects of central exams on student test scores. But critics warn that these effects may arise through the strategic behavior of students and teachers, which may not affect human capital accumulation in the long run. Exploiting variation in examination types across school systems and over time, we provide the first evidence that central exams positively affect adult skills. However, our estimates are small compared to the existing estimates for students, which may indicate some fade-out in the effect on skills over time.
Keywords: I20; J24; J31; 330; central exams; adult skills; earnings; PIAAC